INTERNALISASI AJARAN YAMA DAN NIYAMA PADA SISWA MELALUI EKSTRAKURIKULER YOGA DI SEKOLAH MENENGAH PERTAMA DWIJENDRA MATARAM - Suparta, Ida Kade (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2018)
Today, yoga has become a world icon as a system of physical exercise that has been practiced by people from diverse backgrounds and has been integrated with their respective social cultures. In fact, especially in Indonesia, yoga has been directed to the formal education is packed in the form of yoga extracurricular activities and not infrequently as a competition and art performances which are integrated with acrobatic art. Yoga has a foundation of universal ethical values called Yama and Niyama which should also be internalized so that yoga is not just a system of physical exercise only. This research researching how to internalize the teachings of Yama and Niyama to the students through the yoga extracurricular at Dwijendra Mataram Junior High School (SMP Dwijendra Mataram) so that known the type of Yama and Niyama teachings are internalized, the supporting and inhibiting factors the internalization process, and know the implications of Yama and Niyama teachings that are internalized. This research is qualitative research by using phenomenology approach. Informants were determined purposively. Data were collected through observation, interview and documentation method, then analyzed by data reduction, data display, and drawing a conclusion. While checking the validity of data that includes credibility, transferability, and dependability, done by using source triangulation techniques, method triangulation, and theory triangulation. The research results obtained, firstly, types of Yama teaching that is internalized is anresangsya. While the type of Niyama teachings that are internalized include ijya and tapah. Secondly, internal support factors include the high interest of the student and better mental characteristics than in previous years, while the external support factor is the role of teachers, yoga extracurricular mentors, and headmaster. Then the internal inhibiting factor is that there are still some students whose interests are low, while the external inhibiting is a simple yoga mat so that the comfort of the exercise has not been guaranteed to the fullest. Thirdly, the teachings of Yama and Niyama that are internalized in the students have an implication to increased student learning motivation and moral ethics.